2018
DOI: 10.1111/rode.12568
|View full text |Cite
|
Sign up to set email alerts
|

Using sparse categorical principal components to estimate asset indices: new methods with an application to rural southeast asia

Abstract: Asset indices have been used since the late 1990s to measure wealth in developing countries. We extend the standard methodology for estimating asset indices using principal component analysis in two ways: by introducing constraints that force the indices to have increasing value as the number of assets owned increases, and by estimating sparse indices with a few key assets. This is achieved by combining categorical and sparse principal component analysis. We also apply this methodology to the estimation of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Data on assets were not available in early life for India. The limited availability of asset data also prevented us from inferring if other metrics associated with assets – quantity, quality or functioning, technological generation, availability of substitutes – biased our findings ( Johnston & Abreu, 2016 ; Merola & Baulch, 2018 ). Our sensitivity analysis using data from the Pelotas 1993 (Brazil) cohort suggested that a harmonized asset index created using counts of assets such as televisions, cars and housekeepers as well as number of bathrooms in the house was correlated (r = 0.98) with the benchmark asset index.…”
Section: Discussionmentioning
confidence: 99%
“…Data on assets were not available in early life for India. The limited availability of asset data also prevented us from inferring if other metrics associated with assets – quantity, quality or functioning, technological generation, availability of substitutes – biased our findings ( Johnston & Abreu, 2016 ; Merola & Baulch, 2018 ). Our sensitivity analysis using data from the Pelotas 1993 (Brazil) cohort suggested that a harmonized asset index created using counts of assets such as televisions, cars and housekeepers as well as number of bathrooms in the house was correlated (r = 0.98) with the benchmark asset index.…”
Section: Discussionmentioning
confidence: 99%
“…The positive scoring factor is closely associated with higher socio-economic status and the negative scoring factor explains the lower socio-economic status. The first principal component will provide a measure of wealth (27) . Hence, the first component of the scoring factor of each asset variables is used for assessing socio-economic status of the sample households.…”
Section: Asset Based Scoring Using Principal Component Analysismentioning
confidence: 99%
“…Later, asset index is sorted and quintile cut-off points created to differentiate economic groups and by caste categories (Government of India classification). The approaches used are based on the assumption that socio-economic status is uniformly distributed or data driven (27) . Arbitrary quintile cut-off points are categorized into five groups: lowest 20 percent of the households into 'poorest' , second lowest 20 percent of the households into 'poor' , mid 20 percent of the households into 'middle' , second highest 20 percent of the households into 'rich' and highest 20 percent of the households into 'richest' .…”
Section: Asset Index Of Different Economic Groups and By Caste Categoriesmentioning
confidence: 99%
“…NLPCA produces a similar output to that of PCA with eigenvalues, component loadings and communalities [9]. Reference [12], also argue the use of NLPCA over other methods stating that the interpretability of the NLPCA solutions are much enhanced compared to MCA solutions as NLPCA produces components that are combinations of the variables instead of categories. Hence, weights for the index can be derived from the NLPCA solution in a similar fashion to that of weights derived using PCA or FA.…”
Section: Introductionmentioning
confidence: 98%
“…In fact, MCA is the oldest application of PCA to categorical variables. However, [12] raise concerns over the interpretability of MCA solutions as they are expressed in terms of combinations of categories for each of the individual variables. This will complicate the interpretability of the MCA results, because MCA yields factorial scores for each level of the categorical variables.…”
Section: Introductionmentioning
confidence: 99%